1992
DOI: 10.1016/0304-3959(92)90140-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of electromyography and muscle palpation in the diagnosis of tension-type headache with and without pericranial muscle involvement

Abstract: The Headache Classification Committee of the International Headache Society recently issued revised diagnostic criteria for headache disorders. According to these criteria, tension-type headache may be subclassified depending upon whether pericranial muscle disorder is found. The presence or absence of pericranial muscle disorder was to be determined by palpating the muscles for tenderness or by measuring electromyographic (EMG) activity. In this study, pericranial muscles were palpated, and EMG activity was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 6 publications
2
29
1
1
Order By: Relevance
“…Elevations in pericranial muscle tenderness observed in this young sample of chronic tension-type headache sufferers are consistent with previous findings from the handful of studies that have assessed this variable in either tension-type headache patients or in representative population samples (Lous and Olesen 1982;Langemark and Olesen 1987;Drummond 1987;Schoenen et al 1991a;Hatch et al 1992;Jensen et al 1992). However, the shortened exteroceptive silent period that has been observed in patient samples of chronic tension-type headache sufferers (Schoenen et al 1987;Nakashima and Takahashi 1991;Schoen en 1993a,b) was not evident in our sample of young chronic tension-type headache sufferers.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Elevations in pericranial muscle tenderness observed in this young sample of chronic tension-type headache sufferers are consistent with previous findings from the handful of studies that have assessed this variable in either tension-type headache patients or in representative population samples (Lous and Olesen 1982;Langemark and Olesen 1987;Drummond 1987;Schoenen et al 1991a;Hatch et al 1992;Jensen et al 1992). However, the shortened exteroceptive silent period that has been observed in patient samples of chronic tension-type headache sufferers (Schoenen et al 1987;Nakashima and Takahashi 1991;Schoen en 1993a,b) was not evident in our sample of young chronic tension-type headache sufferers.…”
Section: Discussionsupporting
confidence: 77%
“…In recent years, research attention has shifted to possible abnormalities in pericranial pain sensitivity and possible abnormalities in central pain modulation. Although results obtained in studies of thermal and pressure pain thresholds have been conflicting (e.g., Schoen en et al 1991a,c;Jensen et al 1993a), when tenderness has been identified by manual palpation, higher levels of pericranial muscle tenderness have been reported in tension-type headache sufferers than in headache-free controls (Lous and Olesen 1982;Drummond 1987;Langemark and Olesen 1987;Schoen en et al 1991a;Hatch et al 1992) or in migraineurs (Lous and Olesen 1982;Schoenen et a1. 1991a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiological background of the association between some symptoms and headache is difficult to clarify. Regarding oral parafunctions, we may hypothesize the possible role of muscular tenderness as a common mechanism involved in the complex pathophysiology of tension-type headache and in the expression of this symptom [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…examination tests (Lous and Olesen 1982;Langemark and Olesen 1987;Bovim 1992;Hatch et al 1992;Garrett et al 1993;Jensen et al 1993;Kidd and Nelson 1993;Watson and Trott 1993;Jensen 1996;Lipchik et al 1996;Sand et al 1997;Zwart 1997;Ashina et al 1999;Jull et al 1999Jull et al , 2007Neufeld et al 2000;Dumas et al 2001;Mørk et al 2003;Giacomini et al 2004;Fernández-de-las-Peñas et al 2006;Fernández-de-Las-Peñas et al 2006a, 2006b, 2007Sandrini et al 2006;Zito et al 2006;Amiri et al 2007;Glaros et al 2007Glaros et al , 2007Ogince et al 2007;Hall et al 2008Hall et al , 2010Hall et al , 2010Bevilaqua-Grossi et al 2009;Peddireddy et al 2009;Uthaikhup et al 2009;Sohn et al 2010Sohn et al , 2013Stuginski-Barbosa et al 2010;Melo et al 2012;Watson and Drummond 2012;Marchand et al 2014;Tali et al 2014). …”
Section: A C C E P T E D Accepted Manuscriptunclassified